Design of a flexible organometallic tecton: host–guest chemistry with picric acid and self-assembly of platinum macrocycles. Issue 6 (23rd January 2017) - Jana, Achintya; Bhowmick, Sourav; Kaur, Supreet; Kashyap, Hemant K.; Das, Neeladri
Abstract : A new "flexible" and ditopic Pt(ii ) organometallic compound is a tecton for the self-assembly of neutral metallacycles. It also exhibits significant binding affinity for picric acid. Abstract : The synthesis and characterization of a new pyrazine-based "flexible" and ditopic platinum(ii ) organometallic molecule (3 ) is being reported. Flexibility in this molecule is due to the presence of ether functional groups that bridge the rigid core and periphery. Due to the presence of square planar Pt(ii ) centers at the two ends, the molecule's potential to act as an acceptor building block in the construction of metallamacrocycles was tested. Upon reaction of3 with various dicarboxylates in a 1 : 1 stoichiometric ratio, [2 + 2] self-assembled neutral metallacycles (M1 –M3 ) were obtained in high yields.M1 –M3 were characterized using multinuclear NMR, high resolution mass spectrometry and elemental analyses. The shape and dimensions of these supramolecular structures were also confirmed by optimizing the geometry using the density functional theory (DFT) approach. Computational studies suggest thatM1 –M3 are nanoscalar macrocyles. Furthermore, using isothermal titration calorimetry (ITC), it was shown that3 can bind with picric acid (PA) to yield a3 ·(PA)2 host–guest complex. The magnitude of the binding constant indicates that3 has significant affinity for PA.